Modern Centers of Qur’anic Recitation and its Positive Effects on Students and the Society in Yobe State - Adamu, Abubakar Ibrahim; Ardo, Hamidu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The study on Islamic Education towards the integration of human knowledge has been of great importance, not only to the general phenomena of education, but also to other disciplines. Modern Centers of Que’anic Recitation known as the formal school or a place where teaching and learning of the Glorious Qur’an and other Islamic sciences is taken place. The system otherwise called Modern Qur’anic school system, it has been in existence centuries prior to the British colonization as a source of moral guidance and educational training for the Muslim particularly in northern part of Nigeria. It has also contributed extremely to promoting Qur’anic education, inculcating self-discipline, spiritual growth of Muslim individuals and the communities respectively. This paper aimed at disclosing the historical development of Modern Centers of Qur’anic Schools and its prospects with particular reference to the countr Nigeria. The research is an exploratory quantitative research that sourced cross sectional Schools data collected through the use of structured questionnaire. Multistage purposive sampling method was employed in selecting the respondents for the study across the study area. Themaic analysis was employed as the method of data analysis. Both descriptive and inferential statistics were used to summarize and interpret the results of the analyses of the data obtained. The findings of this research revealed that, Modern Centers of Qur’anic is a center that produced Qur’anic memorizers that can participate in any Qur’anic Competition around the grobe. It further revealed that, Modern Centers of Qur’anic Recitation produced Imams, good leaders and Righteous people in Yobe State. It revealed that, Modern Centers of Qur’anic Recitation have developed rapidly since its establishment irrespective of some prevailing problems and they make a positive contribution on the society in terms of spiritual, moral and social wellbeing as well as their Techniques of Teaching Tajwid. Finally, the recommended that public awareness campaigns should be carryout to address hinderances of sending small children to Tsangaya schools.